Estimating the costs of crime in New Zealand in 2003/04 - Andrew Thompson
We estimate that the total costs of crime in New Zealand in 2003/04 amounted to $9.1 billion. Of this, the private sector incurred $7 billion in costs and the public sector $2.1 billion. Offences against private property are the most common crimes but offences against the person are the most costly, accounting for 45% of the total estimated costs of crime. Empirically-based measures like those presented here – the total and average costs of crime by category – are a useful aid to policy analysis around criminal justice operations and settings. However, care needs to be taken when interpreting these results because they rely considerably on assumptions, including the assumed volume of actual crime, and the costs that crime imposes on victims. This difficulty in constructing robust estimates also implies that care should be taken not to draw conclusions about whether the Government should be putting more or less resources into any specific categories of crime, based on their relative costs alone.crime; justice; costs; New Zealand